Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1155/2016/1858202
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Aspects of Fulminant Type 1 Diabetes in Chinese

Abstract: Background. Fulminant type 1 diabetes (FT1D) is a novel subtype of type 1 diabetes characterized by extremely rapid onset and complete deficiency of insulin due to the destruction of pancreatic β cells. However, the precise mechanisms underlying the etiology of this disease remain unclear. Methods. A total of 22 patients with FT1D and 10 healthy subjects were recruited. Serum antibodies to GAD, IA2, and ZnT8 in patients were tested. And peripheral T cell responses to GAD65, insulin B9–23 peptide, or C peptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 22 publications
2
10
0
1
Order By: Relevance
“…The involvement of autoimmune T cell was described firstly as detection of the high level of serum C‐X‐C motif chemokine 10 (CXCL‐10) and islet antigens reactive T cells in peripheral blood of FT1D patients 78 . Similar results were observed in subsequent studies, while islet‐related antigens reactive T cells were found only in partial FT1D patients while the prevalence varied widely in distinct examines 3,79‐84 . Moreover, it is observed in the autopsied pancreas that CXCL‐10 secreted by β cells could attract autoreactive T cells and macrophages through CXCR‐3 (CXC chemokine receptor 3).…”
Section: Adaptive Immunity Including Cellular Immunity and Humoural Isupporting
confidence: 53%
“…The involvement of autoimmune T cell was described firstly as detection of the high level of serum C‐X‐C motif chemokine 10 (CXCL‐10) and islet antigens reactive T cells in peripheral blood of FT1D patients 78 . Similar results were observed in subsequent studies, while islet‐related antigens reactive T cells were found only in partial FT1D patients while the prevalence varied widely in distinct examines 3,79‐84 . Moreover, it is observed in the autopsied pancreas that CXCL‐10 secreted by β cells could attract autoreactive T cells and macrophages through CXCR‐3 (CXC chemokine receptor 3).…”
Section: Adaptive Immunity Including Cellular Immunity and Humoural Isupporting
confidence: 53%
“…Kotani et al reported that 9 of 13 (69.2%) GAD-reactive Th1 cells and 3 of 12 (25%) insulin-B9-23-reactive Th1 cells were identified in FT1DM by the ELI-SPOT assay [23]. Wang et al found that GAD-stimulated interferon-γ (IFN-γ) and both insulin-and C-peptidestimulated IFN-γ spots were detected in some cases in the Chinese FT1DM population [24]. These results suggested that autoimmune responses might contribute, at least in part, to the development of FT1DM.…”
Section: Discussionmentioning
confidence: 99%
“…Haseda et al found that anti-CD300e antibody is a novel biomarker that can help diagnose fT1D [7]. Wang et al found that the expression of IFN-γ significantly increased in peripheral blood mononuclear cells of fT1D patients indicating that autoimmune responses are related to fT1D in Chinese patients [8]. Nagafuchi et al found that TYK2 mutation may be associated with the susceptibility of virus-induced fT1D with flu-like symptoms, and the risk of anti-GAD antibody-negative patients significantly increased compared with anti-GAD antibody-positive patients [9].…”
Section: Discussionmentioning
confidence: 99%